Are late-born young soccer players less mature than their early-born peers, although no differences in physical and technical performance are evident? - Bezuglov, E.; Malyakin, G.; Emanov, A.; Malyshev, G.; Shoshorina, M.; Savin, E.; Lazarev, A.; Morgans, R. (Sports, 2023)
The aim of the study was to compare the status of somatic maturity, anthropometry, strength, speed, and soccer-specific technical skills of players from leading youth soccer academies born in different quarters of the same calendar year. A total of 678 young male soccer players from eight leading Russian soccer academies took part in the study. The following anthropometric measures and physical characteristics were measured: height, weight, body mass index, countermovement jumps (CMJ), 5, 10, and 20 m sprints, speed dribbling, foot and body ball juggling, and short and long pass accuracy. The determination of somatic maturity as a percentage of projected adult height was collected. All subject dates of birth were divided into four quartiles according to the month of birth. The analysis of all data obtained was conducted both within the total sample and by quartiles of birth, according to the age group categories of 12-13 years, 14-15 years, and 16-17 years and the degree of somatic maturity. There was a widespread relative age effect, with 43.5% of early-born players and only 9.6% of late-born players representing the sample. Early-born players were more mature than late-born players (p < 0.001 and p < 0.001) but had no statistically significant differences in strength, speed, or soccer-specific skills.